Enterovirus 75, a new pathogenic virus in Granada province (Spain) - Reina-González, Gabriel; Pérez-Ruiz, Mercedes; Avellón, Ana; Trallero, Gloria; Otero, Almudena; de la Rosa-Fraile, Manuel; Jiménez-Valera, María; Navarro-Marí, José María (Enfermedades infecciosas y microbiología clínica, 2007)
Members of the genus Enterovirus are usually investigated for their etiological role in neurological syndromes. However, they are often associated with other syndromes such as febrile illness, acute respiratory infection and exanthema. In this study, clinical and epidemiological data from five subjects with infection by the recently described enterovirus 75 were analyzed in the province of Granada (Spain). Diagnosis at the genus level was carried out by viral culture in MRC-5 and rhabdomyosarcoma cell lines. Isolate serotypes were determined by RT-PCR of a fragment of the VP1 region and subsequent sequencing of the PCR products. Among the five enterovirus 75 isolated, two were detected in children with aseptic meningitis (1 month and 12 years old) and three in subjects with non-neurological syndromes, i.e. acute respiratory infection, febrile illness and gastroenteritis (all were aged less than one year). The five cases were detected between December 2005 and May 2006. All patients recovered without sequelae. These data demonstrate that enterovirus 75 circulates in the south of Spain and indicate that this enterovirus serotype may be implicated in less severe non-neurological syndromes, particularly in younger children, and mainly during the cold months of the year.